Depositional Evolution of the Western Amundsen Basin, Arctic Ocean: Paleoceanographic and Tectonic Implications. Issue 12 (12th December 2018) - Castro, Carlos F.; Knutz, Paul C.; Hopper, John R.; Funck, Thomas
Abstract: A new stratigraphic model and estimated sedimentation rates of the western Amundsen Basin, Arctic Ocean, are presented based on multichannel seismic reflection data, seismic refraction data, magnetic data, and integrated with the sedimentary sequence from the central Arctic Ocean, obtained during the Arctic Coring Expedition. This places new constraints on the postbreakup Cenozoic depositional history of the basin, the adjacent Lomonosov Ridge, and improves the understanding of the tectonic, climatic, and oceanographic conditions in the central Arctic region. Four distinct phases of basin development are proposed. During the Paleocene‐mid‐Oligocene, high sedimentation rates are linked to terrestrial input and increased pelagic deposition in a restricted basin. Deposition of sedimentary wedges and mass transport into marginal depocenters reflect a period of tectonic instability linked to compression associated with the Eurekan Orogeny in the Arctic. During the late Oligocene‐early Miocene, widespread passive infill associated with hemipelagic deposition reflects a phase of limited tectonism, most likely in a freshwater estuarine setting. During the middle Miocene, mounded sedimentary buildups along the Lomonosov Ridge suggest the onset of geostrophic bottom currents that likely formed in response to a deepening and widening of the Fram Strait beginning around 18 Ma. In contrast, the Plio‐Pleistocene stage is characterized by erosional features such as scarps and channels adjacent to levee accumulations, indicative of a change to a higher‐energy environment. These deposits are suggested to be partly associated with dense shelf water‐mass plumes driven by supercooling and brine formation over the northern Greenland continental shelf. Key Points: New multichannel seismic reflection data constrain the Cenozoic depositional history of the Amundsen Basin in the Arctic Ocean Four key development stages explain the basin evolution based on facies interpretation and estimated sedimentation rates Plio‐Pleistocene cascading plumes, possibly from brine formation, affected the North Greenland shelf and influenced deep circulation